Future Labor Training Teachers Engineering Training at a Higher Educational Establishment: Realities and Prospects - Kurok, Vira (Pedagogical Discourse, 2015)
The need to improve the future Labor training teachers’ engineering training caused by forming the ability to adapt to changes in the field of technics and production technology, to creatively performing professional tasks. It is stressed that engineering training gives future specialist the opportunity to be aware of general questions of technical mechanisms structure and their usage as well as the opportunity to know the history and perspectives of technics development. It is stated that there is still a tendency to teach engineering disciplines like the higher education establishments of technical profile do, though the goal and tasks of their teaching is radically different from those that future engineers have to implement. The need of teachers’ engineering training connection with general and methodical ones is emphasized in the article as future specialists should be able to transmit engineering knowledge received at the university to their future pupils. The Labor training teacher’s pedagogical activity embodies the three major, closely interrelated aspects: pedagogical, psychological and technical (or engineering). Using the historical teaching material is defined as the way of engineering training optimizing and the opportunity to master it while teaching technical disciplines are suggested. The problem of teacher’s training who has not only knowledge of psychological and pedagogical sciences and the specialties but who is also deeply aware of the nature of pedagogical creativity, has qualities of the researcher, clearly realizes the peculiarities of forming technical thinking as a result of assimilation and application of engineering knowledge and skills is also characterized. It is noted that the Labor training teacher should not only transmit his/her knowledge and skills to pupils (though for this purpose the technical literacy is also required) but also provide the material and technical base of school workshops by necessary equipment and devices. Today engineering knowledge and skills are actual because of involving pupils to social work and project activities. Improving the future Labor training teachers engineering training at the university should be directed at implementing the general objectives of the educational sector «Technology».